Assessing different diagnostic tests for gastroesophageal reflux disease: a systematic review and network meta-analysis - Zhang, Mengyu (Therap Adv Gastroenterol, 2019)
BACKGROUND: The aim of the current systematic review and network meta-analysis (NMA) was to assess the diagnostic characteristics of the gastroesophageal reflux disease questionnaire (GERDQ), proton-pump inhibitor (PPI) test, baseline impedance, mucosal impedance, dilated intercellular spaces (DIS), salivary pepsin, esophageal pH/pH impedance monitoring and endoscopy for gastroesophageal reflux disease (GERD). METHODS: We searched PubMed and the Cochrane Controlled Trial Register database (from inception to 10 April 2018) for studies assessing the diagnostic characteristics of the GERDQ, PPI test, baseline impedance, mucosal impedance, DIS, or salivary pepsin and esophageal pH/pH impedance monitoring/endoscopy in patients with GERD. Direct pairwise comparison and a NMA using Bayesian methods under random effects were performed. We also assessed the ranking probability. RESULTS: A total of 40 studies were identified. The NMA found no significant difference among the baseline impedance, mucosal impedance, and esophageal pH/pH impedance monitoring and endoscopy in terms of both sensitivity and specificity. It was also demonstrated that the salivary pepsin detected by the Peptest device had comparable specificity to esophageal pH/pH impedance monitoring and endoscopy. Results of ranking probability indicated that esophageal pH/pH impedance monitoring and endoscopy had highest sensitivity and specificity, followed by mucosal impedance and baseline impedance, whereas GERDQ had the lowest sensitivity and PPI test had the lowest specificity. CONCLUSIONS: In a systematic review and NMA of studies of patients with GERD, we found that baseline impedance and mucosal impedance have relatively high diagnostic performance, similar to esophageal pH/pH impedance monitoring and endoscopy.